Cilostazol-induced relaxation of calf cardiac vein and coronary artery during cooling - (:unkn) unknown (COMENIUS UNIV, 2013)
Objective: At present very little is known about the role of endothelial nitric oxide (NO) in the effects of temperature on vascular reactivity. The aim of the present study is to evaluate the influence of cooling (to 28 degrees C) on the vasodilatation induced by cilostazol(10(-9)-3x10(-4)M) on carbachol (10(-6))-precontracted calf cardiac vein and coronary artery and the role of NO in these effects. Materials and methods: Ring preparations of great cardiac vein and the anterior interventricular branch of left coronary artery were used. Results: Cilostazol produced concentration-dependent relaxation of calf cardiac vein and coronary artery rings precontracted with carbachol. During cooling, the pIC(50) values, but not the maximal responses to cilostazol were significantly lower than at 37 degrees C in both preparations. Cooling to 28 degrees C in the presence of N-G-nitro-L-arginine methyl ester (L-NAME, 10(-4) M) did not modify the effect of temperature both in cardiac vein and coronary artery. These results demonstrate for the first time that cooling-induced changes of cilostazol in calf cardiac vein and coronary artery are independent of NO (Tab. 2, Fig. 3, Ref. 32). Full Text in PDF www.elis.sk.
Keywords: cardiac vein; cilostazol; cooling; coronary artery; nitric oxide; ENDOTHELIUM-DEPENDENT RELAXATION; CYCLIC-NUCLEOTIDE PHOSPHODIESTERASES; NITRIC-OXIDE; FEMORAL ARTERIES; RABBIT EAR; PULMONARY-ARTERY; INHIBITOR; CONTRACTIONS; AUGMENTS; CHANNELS